Seeing reason or seeing costs? The United States, counterterrorism, and the human rights of foreigners. (March 2022) - Heupel, Monika; Heaphy, Caiden; Heaphy, Janina
It is well known that in the wake of 9/11, the United States committed various extraterritorial human rights violations, that is, human rights violations against foreigners outside of its territory. What is less known is that the United States has gradually introduced safeguards that are, at least on paper, meant to prevent its counter-terrorism policies from causing harm to foreigners abroad or, at least, to mitigate such harm. Based on three case studies on the development of safeguards related to torture, targeted killing, and mass surveillance, we show that two mechanisms, coercion and strategic learning, deployed either on their own or in combination, can account for the development of such safeguards. By contrast, we found no evidence of a third mechanism, moral persuasion, having any direct effect. In other words, US policymakers opt to introduce such safeguards either when they face pressure from other states, courts, or civil society that makes immediate action necessary or when they anticipate that not introducing them will, at a later date, result in prohibitively high costs. We did not find evidence of US policymakers establishing safeguards because they deemed them morally appropriate. From this we conclude that, although the emerging norm that states have extraterritorial (and not just domestic) human rights obligations may not have been internalized by key US policymakers, it nevertheless has a regulative effect on them insofar as the fact that relevant others believe in the norm restricts their leeway and influences their cost–benefit calculations.